Diffusion-weighted imaging or computerized tomography perfusion assessment with clinical mismatch in the triage of wake up and late presenting strokes undergoing neurointervention with Trevo (DAWN) trial methods. Issue 6 (August 2017) - Jovin, Tudor G; Saver, Jeffrey L; Ribo, Marc; Pereira, Vitor; Furlan, Anthony; Bonafe, Alain; Baxter, Blaise; Gupta, Rishi; Lopes, Demetrius; Jansen, Olav; Smith, Wade; Gress, Daryl; et al.
Rationale: Efficacy of mechanical thrombectomy for acute stroke due to large vessel occlusion initiated beyond 6 h of time last seen well has not been demonstrated in randomized trials. Aim: To establish whether subjects considered to have substantial areas of salvageable brain based on age-adjusted clinical core mismatch who can undergo endovascular treatment within 6–24 h from time last seen well (TLSW) have better outcomes at three months compared to subjects treated with standard medical therapy alone. Age-adjusted clinical core mismatch is defined by age (≤80 or >80 years), baseline National Institutes of Health Stroke Scale (NIHSS) (10–20 or ≥21), and core size (0–20 cm 3 in subjects older than 80 and, in subjects younger than 80, 0–30 cm 3 with NIHSS 10–20 and 31–50 cm 3 with NIHSS ≥21). Design: Prospective, randomized, multicenter, Bayesian adaptive-enrichment, open label trial with blinded endpoint assessment. For the purpose of enrolment, ischemic core size will be evaluated by CT perfusion or magnetic resonance imaging-diffusion-weighted imaging measured by automated software (RAPID). Procedures: Subjects with acute ischemic stroke due to computed tomography angiography- or magnetic resonance angiogram-proven arterial occlusion of the intracranial internal carotid and/or proximal middle cerebral artery (M1) with age-adjusted clinical core mismatch in whom treatment can be initiated between 6 and 24 h from TSLW are randomized in a 1:1 ratio to receive mechanical embolectomy with the Trevo device or medical management alone. Sequential interim analyses allowing adaptation of enrolment criteria or stopping new enrolment for futility or predicted success will occur in every 50 randomized patients starting at 150 to a maximum of 500 patients. Study outcomes: The primary endpoint is the modified Rankin Scale score at 90 days. The primary safety outcome is stroke-related mortality at 90 days. Analysis: The primary endpoint, expressed as a utility-weighted modified Rankin Scale score is analyzed using a Bayesian posterior probability with adjustment for ischemic core size. For regulatory reasons, a nested co-primary endpoint analysis was added consisting of the proportion of subjects with modified Rankin Scale 0–2 between the active and control groups also analyzed using a Bayesian model.